(untitled) (Biological Sciences - PJSIR, 2007)
. The study, designed to assess the potentials of oven dried Amaranth us spinosus leaf meal as parti a l replacement for soybean cake i n the diet of Nile Ti lapia, revealed no significant di fference (P> 0.05) in feed and protei n i ntake. Fish fed on Amaranthus spinosus leaf meal diets had significant (P<0.05) higher survival percentage , whi le that on soybean cake meal (control diet) recorded significant (P<0.05) better weight gain, average dai l y rate of growth, efficient feed and protei n utili zation as wel l as average final weight.